Two-level hiding an encrypted image - Faten H. MohammedSediq Al-Kadei (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Encryption and hiding images are becoming a hot research area and a broad prospect for application. This article uses a secure algorithm with Low Significant Bit method to hide an encrypted high-resolution color bitmap image in two selectively color images (i.e., two cover images). The paper introduces a two-level hiding encrypted image using MATLAB-GUI programming language. In the beginning, with a key image using XOR bit operation, the original RGB image is encrypted. After that, the encrypted image is hidden into the first cover image. The cover image is then hidden into another cover to make the secret image safer without changing the perceptual quality for both covers. Then, the algorithm is tested on many bitmap images, which can be an important image, fingerprint image, samples of secret medicine, or bank account pattern. The correlation histograms demonstrate a high correlation for all encrypted images. The PSNR is used to find steganography quality for the two cover images after hiding the secret image showing a high quality for the two levels of hiding operation